On the translation of the attributive sentence from Arabic into Spanish - Aarab, Abderrahim (Estudios de Traducción, 2013)
In this paper, we propose to study the translation of the Arabic attributive structure and its syntactic variants ’inna y kāna. For us, syntax causes serious problems in the translation process, since each language has its own building and structuring procedures that hinder the task of the translator. In this sense, we will study the concept of attribution in the Spanish and Arabic grammar in order to find the equivalences and differences between Arabic and Spanish attributive sentence, ​​and therefore make them available to the task of translation in the two languages.